A Language for Organization Design: Part II - Ansoff, H. I.; Brandenburg, R. G. (Management Science, 1971)
This paper develops a language for designing the structure of a purposive organization so as to maximize organizational performance potential for achieving given objectives. Four categories of performance attributes are specified, each contributing to the particular objectives an organization pursues in seeking maximum return from the resources it employs: steady-state efficiency, operating responsiveness, strategic responsiveness, structural responsiveness. A fifth category, decision and information quality criteria, further contributes to organizational success. These five types of criteria, combined with tests of economic and human resource feasibility, are used to select and tailor one of several basic organizational forms to meet the particular needs of a firm. Basic organizational forms, observable in business practice, analyzed with respect to the above performance attributes, include: centralized functional form, decentralized divisional form, project management form, innovative form. Several variations on these forms, which have been used in business, are listed along with conditions for the applicability of each, reflecting the need for individual firms to adapt basic structures to suit their distinctive requirements. Major steps in the logic of the overall design process are specified.